PHILOSOPHICAL PROBLEMS OF ECOLOGICAL SAFETY OF MANKIND - Mariana A. Basilaia (Advanced Engineering Research, 2010)
Actual problems of life safety, ecological safety and harmonious society and nature interaction in the «person-nature» system are considered.